Transmission of price shocks and volatility spillovers across the major onion markets in India - Raka Saxena; Ranjit Kumar Paul; Rohit Kumar (Agricultural Economics Research Review, 2023)
This paper studies the price transmission and volatility spillover effects in the major wholesale onion markets in India. It attempts to determine the extent to which price shocks and volatility are transmitted between markets. The persistence of volatility is high, and sudden supply or climate shocks trigger onion prices. Continual surveillance—especially in strategic markets like Lasalgaon, Pimpalgaon, and Bengaluru—can prevent extreme events by examining the extent of price influences and providing advance price signals. Early warning systems based on ‘Big Data’ and ‘Artificial Intelligence’ can help provide advance signals and prevent chaotic events.